Empowerment of beneficiaries in community development: understanding the concept and examining present practices - Md Yassin, Sulaiman; Abu Samah, Asnarulkhadi; Mohamed Shaffril, Hayrol Azril; Hassan, Md Salleh; Othman, Mohd Shahwahid; Abu Samah, Bahaman (Centre for Extension, Entrepreneurship and Professional Advancement (APEEC), Universiti Putra Malaysia, 2010)
The term empowerment has fast become the currency in many development projects involving beneficiaries, where their meaningful participation is deemed to be worthwhile and crucial to the success of such projects. Several techniques have been used in the past and lessons can be found as to the successes and failures of several approaches. However, many development agencies are still grappling with what should be the plausible components of an empowerment model and it remains to be further studied and discussed by experts and practitioners. This paper shall examine and analyse some examples of empowerment concepts and experiments in the past as well as relate to current and on-going empowerment strategies being developed and experimented with in Malaysia and in other countries. Salient constructs found to be successfully implemented and those that have failed shall be duly highlighted and discussed as to why they had been significant factors. Further discussion shall be made on the prospects of empowerment strategies in extension activities in the future.